Drivers and spatial modelling of soil organic carbon in Argentinian subtropical forests: path towards sustainable management and climate mitigation - Manrique, Silvana M.; Gaitan, Juan José; Balducci, Ezequiel Diego; Speranza, Flavio Cesar; Blundo, Cecilia; Gasparri, Ignacio; Zavala, Miguel A.; Peri, Pablo Luis (Elsevier, 2025)
Tropical and Subtropical Moist Broadleaf Forests (TSMF) can constitute important carbon stocks essential for nature-based solutions (NBS) that contribute not only to global warming mitigation efforts but also to multiple human well-being objectives and biodiversity benefits. However, the carbon stock potential of forest soils has not yet been sufficiently studied and valued, although at least a quarter of the world’s soil organic carbon (SOC) stocks have already been lost. The objectives of this work were: 1) to quantify the SOC stock in the existing TSMF in northwestern Argentina (called Yungas ecoregion); 2) to explore and identify the main drivers defining the SOC stock: 3) to model and map the SOC stock in the ecoregion. Subtropical rainforest soils in Argentina store about 298,090 Gg of SOC for an area of 35,409 km2. Converting forested areas to agriculture can reduce the SOC by up to 60 %. This reserve could be increased through active carbon sequestration mechanisms. Stand density, sand content and elevation are the main drivers of SOC in the ecoregion. Understanding how these factors influence the distribution of SOC can help assist to design more sustainable land-use practices, with the aim of promoting and preserving its SOC storage. The generated information and spatial models thus constitute a scientific basis for mitigation policies, where NBS could be fundamental implementation strategies with multiple co-benefits.